MODIFIKASI ALAT SORTASI GABAH (ORIZAE SATIVA L) - Syasmar, Andi Musawwirul Munir; Lahming, Lahming; Jamaluddin, Jamaluddin (Universitas Negeri Makassar, 2019)
This study aims to modify the grain sorting tool and test the working capacity of the tool. The method of this research is design research, the results of the study were processed using quantitative data analysis techniques with descriptive statistics. The trial in this study is only limited to the tool test, so the data obtained is presented in the form of a table from the results of the trial. The design of grain sorting equipment through several mechanisms including frame making, hopper, sieve, filled grain channel, casing installation, and other components. The grain sorting tool can work ergonomically according to the design and the average capacity is 199.51 kg / hour